Mechanical properties of natural gas wellbore structure under non-uniform load - Dongyin LI; Mingliang LI; Wen WANG; Yuxi HAO; Shen WANG; Hongbin LI (Meitan kexue jishu)
In areas where natural gas and coal resources overlap, the movement of overburden caused by high-intensity coal mining causes radial compression and deformation or even destruction of the natural gas well body structure within the protective coal pillar. The natural gas diffused from the damaged area can easily lead to fire, explosion or personnel poisoning accidents in coal mines. In order to verify the mechanical properties of the natural gas well bore structure under the influence of cross-mining of natural gas and coal, four types of casing and cement ring combination were designed according to the well structure, and the complex radial stress model of natural gas well structure is simplified into a one-way force model. Digital Image Correlation (DIC) technique and RMT-150 rock mechanics instrument were used to carry out radial compression test and DIC test of casing cement ring combination. Finally, the mechanical performance mechanism of wellbore structure is analyzed from the perspective of deformation rates and force transfer laws of different materials. The results showed: The mechanical properties of the well structure with the outermost casing layer are significantly superior to those of the well structure with the outermost cement sheath. The mechanical performance of the well structure is related to the material’s rate of deformation and the principles governing force transmission. When the composite specimen is acted on by external force, the force transmission law gradually decreases from the outside to the inside, and the outermost layer of the specimen receives the largest force. When the outermost layer of the wellbore structure is a cement sheath, the structure as a whole is brittle. Since the deformation rate of the cement sheath is greater than that of the casing, cracks appear at the cement sheath and casing bonding surface. The cement sheath is prone to brittle fracture under tensile stress. When the casing is the outermost layer of the wellbore structure, the whole structure is elastic-plastic. Under the load, the outer casing first undergoes compression deformation, and the inner cement ring produces internal cracks under the extrusion of the casing, but it does not break under the constraint of the casing, and the whole specimen is damaged by radial compression deformation.